Reduction of Organic Waste Using Black Soldier Fly Hermetia illucens Larvae (BSF) Technology - Putra, Firmanudin Yuga; Ratnawati, Rhenny; Widyastuti, Sri (Jurnal Ilmu Alam dan Lingkungan, 2025)
The waste problem is a significant issue faced by developing countries like Indonesia. It is caused by the increasing population and economic growth, leading to a rise in waste generation. The objective of this studi was to examine the efficiency of feed types on the development of BSF larvae in decomposing organic waste and to study the final reduction in organic waste levels after being decomposed by BSF larvae. Three types of processing media reactors were used for a duration of 14 days, with each reactor being treated differently. The M1 reactor the composition of the type of waste given to BSF larvae in the M1 reactor is organic waste, especially rice waste and vegetable waste with a total amount of 5 kg, then 5 kg of tofu waste is added as a change and comparison to the composition of the feed in the M1 reactor. The M2 reactor is organic waste, especially rice and vegetable waste, with a total amount of 10 kg. The M3 reactor is tofu dregs waste with a total amount of 10 kg. This research showed that the conversion efficiency value of feed digested by BSF larvae, in M1 which gets an ECD value of 10.47%, then reactor M2 gets an ECD value of 5.65%, while in the M3 reactor the highest ECD value was obtained with a value of 11.67%. The final water content of organic waste is a range of 53.43-58.49%. The final pH value in the range of 5.90-7.10. The C/N ratio final in a range of 11.92-15.74.